Photosynthetic Induction Characteristics in Saplings of Four Sun-Demanding Trees and Shrubs - Qiuping Liu; Wei Jin; Liying Huang; Danfeng Wang; Kedong Xu; Yunmin Wei (Plants)
Light serves as the unique driving force of photosynthesis in plants, yet its intensity varies over time and space, leading to corresponding changes in the photosynthetic rate. Here, the photosynthetic induction response under constant and fluctuating light was examined in naturally occurring saplings of four sun-demanding woody species, Eucalyptus. Ficus macrocarpa L., Hibiscus syriacus L. and Ficus carica L. We aimed to find out the relations among gas exchange parameter adaptions among different species during photosynthetic induction. The net photosynthetic rates (A) versus time course curves were sigmoidal or hyperbolic after the dark-adapted leaves were irradiated by continuous saturated light. Compared with other species, Ficus carica L. have the largest net photosynthesis rate, stomatal conductance to CO2 (gsc), and the maximum carboxylation rate (Vcmax) at both the initial and steady photosynthetic state. The initial gsc (gsci) was as much as sixfold higher compared to the other shrub, Hibiscus syriacus L. The time required to reach 90% of A (tA90) was 7–30 min; tA90 of Ficus carica L. and Ficus macrocarpa L. were lower than that of the other two species. The time required to reach 90% of gsc (tgsc90) significantly lagged behind tA90 among species. Biochemical induction was fast in leaves of Ficus carica L., as about 4 min were needed to reach 90% of Vcmax, while the other species needed 7–18 min. Correlation analysis showed that the tgsc90 was the main factor in limiting tA90, especially for Eucalyptus spp. and Hibiscus syriacus L.; gsci was negatively correlated with tgsc90 among species. Moreover, time-integrated limitation analysis revealed that gsc still accounted for the largest limitation in constraining A of Eucalyptus spp. and Hibiscus syriacus L. and Ficus macrocarpa L. Overall, the findings suggest that to enhance the carbon gain by woody species under naturally dynamic light environments, attention should be focused on improving the rate of stomatal opening or initial stomatal conductance.